POTENSI GOA MARIA SENDANG JATININGSIH SEBAGAI OBJEK WISATA ROHANI DI DAERAH ISTIMEWA YOGYAKARTA - Krestanto, Hery (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
This research aims to give knowledge about Jatiningsih Sendang Maria Cave as a potential spiritual tourism object, a place of pilgrimage and increasing knowledge of the Christian community about Jatiningsih Sendang Maria Cave. The type of this research is a qualitative research. An observation and interview method is needed to get the data of the research. This research focuses on the potential of Jatiningsih Sendang Maria Cave as a spritual tourism object. The results of this research indicate that the potential of Jatiningsih Sendang Maria Cave as a spiritual tourism object in Yogyakarta, it can be reached by riding various types of vehicles such as motorcycles, cars, tourist buses. Jatiningsih Sendang Maria Cave is located approximately 20 km to the west of monument Jogja.